Podcasts: a new form of knowledge transfer. Scientific discussion in the age of digital native. - Frech, Constanze; Kusché, Sarah (Forum Landschaftsplanung - AbsolventInnenverband, 2020)
Science communication and spatial planning lack attention in the general public. Researchers combat this challenge by adding new media formats such as podcasts to their toolbox. But how did this format gain popularity and is it useful for science communication? What type of communication does spatial planning need? Taking a practical approach to the topic, the team of the spatial planning podcast 'breaking paradigms' gives insights and shares their perspective on podcasting.
Keywords: Wissenschaft; Kommunikationsmedium; Raumplanung; Podcast; Audioblogging; Wissenschaftskommunikation